Creative industriesin the Arab world....The way tosustainable economic growth - leqaa’ Shaker Abbood (Journal of Madenat Alelem University College, 2014)
The developing changes that have taken place during the second half of the twentieth century produced the new economy dominated by ideas and intangible assets and creative skills, a creative economy, which has been associated with the emergence of the knowledge economy and the increasing focus on innovation, research and development and investment in information and communication technology.Education and training as engines are essential to the economics of the century and became the creative industries sector dominant in business and commerce , and has achieved the wealth of exceptional for many Western economies, which realized its importance as a source of value -added the discussion dealt with the creative industries in the Arab world in an attempt to explore the role of economic size and research found that these industries have little attention in some Arab countries and its weak economic and earnings from a few industries as simple as that Arab countries do not have access to mechanisms and stimulate this economy.